The emerging social scientific communication of COVID-19: Semantic bibliometric analysis in SCOPUS - Díaz Herrera, Claudio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The article aims to elucidate how the social scientific communication of COVID-19 is expressed in symbolically generalized media of Scopus. A mixed approach was used to study 301 publications through a structural and semantic dimension. The results show Spanish institutions as the most productive, where five categories emerge semantically: 1. COVID as a pandemic, sanitary and confinement expression; 2. Education and teaching-learning processes; 3. Virtuality, technology and digitalization; 4. Communication, media and information responsibility and; 5. Rights. Axes which are always expressed from the sociocultural concern in a pandemic and epidemiological context.